Efeitos do cloreto de sódio sobre o desenvolvimento e absorção de nutrientes na cultura da berinjela. - Bosco, Maria Regília de Oliveira (2006)
The egg-plant (Solanum melongena L.), a subtropical herb species that botanically belongs to Solanaceae family, much consumed all over the world. On certain areas shortages both the water availability and the water salinity level represent a great limitation for egg-plant plant cultivation. However, almost no information is available related to the egg-plant salt tolerance. With the objective to evaluate the crop salt tolerance, as well as the effects of the different solution nutrition salinity levels on plant growth, an experiment was conducted under greenhouse conditions. The statistical design consisted of ten salinity treatments corresponding to the nutrition solutions CE´s of: 1.70; 2.28; 2.60; 3.11; 4.08; 6.03; 8.12; 10.15; 12.10 and 14.10 dS.m- 1. It was used an entirely statistical randomized block design with three replications. The best results showed that the salinity significantly reduced both plant upper part growth and root production, mainly in the treatments with nutrition solution CE value higher than 3.11 dSm-1. The average leaf-peciole and root contents of K, Ca, Mg, S, Cu, Fe and Mn varied, presenting significant statistical differences. The Na content increased progressively with CE, while the K content decreased in the same way. The increasing salinity levels cause reductions in photosynthesis, transpiration and stomatal conductance.